Airway hydration and COPD - Ghosh, Arunava (Cell Mol Life Sci, 2015)
Chronic obstructive pulmonary disease (COPD) is one of the prevalent causes of worldwide mortality and encompasses two major clinical phenotypes, i.e., chronic bronchitis (CB) and emphysema. The most common cause of COPD is chronic tobacco inhalation. Research focused on the chronic bronchitic phenotype of COPD has identified several pathological processes that drive disease initiation and progression. For example, the lung’s mucociliary clearance (MCC) system performs the critical task of clearing inhaled pathogens and toxic materials from the lung. MCC efficiency is dependent on: (1) the ability of apical plasma membrane ion channels such as the cystic fibrosis transmembrane conductance regulator (CFTR) and the epithelial Na(+) channel (ENaC) to maintain airway hydration; (2) ciliary beating; and (3) appropriate rates of mucin secretion. Each of these components is impaired in CB and likely contributes to the mucus stasis/accumulation seen in CB patients. This review highlights the cellular components responsible for maintaining MCC and how this process is disrupted following tobacco exposure and with CB. We shall also discuss existing therapeutic strategies for the treatment of chronic bronchitis and how components of the MCC can be used as biomarkers for the evaluation of tobacco or tobacco-like-product exposure.